Pertumbuhan Dan Efisiensi Pakan Ikan Nila (Oreochromis Niloticus) Yang Diberi Pakan Buatan Berbasis Kiambang - Rina Iskandar; Elrifadah Elrifadah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The specific objective of this study was to determine the growth and feed efficiency in tilapia (Oreochromis niloticus) fed artificial diets based kiambang that has been fermented with Rhyzopus oryzae. This research are done in May and November 2014, using a completely randomized design. Treatments are different stocking density is 50 individual / m2 (A), 75 individual / m2 (B), and 100 individual / m2 (C). The results showed: the highest relative growth rate in treatment C for 898,0g / individual, followed by treatment B for 679,25g / individual and A of 455,83g / individual. Feed efficiency ranged between 89.65% - 90.26%. The survival rate of tilapia during the maintenance period is 100%. Results of water quality analysis showed decent range for the life of tilapia where the temperature ranges from 26 ° C - 28 ° C, the degree of acidity (pH) ranged from 7.10 to 7.27, and dissolved oxygen (DO) ranged from 3.5 to 4.1 mg / l.